Contributing factors of utero-vaginal prolapse among women attending in Lumbini Medical College and Teaching Hospital - Acharya, S (Journal of Chitwan Medical College, 2017)
Uterine prolapse- is a major public health problem in Nepal. It is a medical and social problem, deeply rooted with poor health services and socio-cultural beliefs. The objective of this study was to find out the contributing factors of utero -vaginal prolapse among women attending at Lumbini Medical College and Teaching Hospital. Descriptive study design was used. A total of 40 women diagnosed with utero-vaginal prolapse were selected as the cases by using purposive sampling technique. Data were collected from 2071/07/8 to 2071/10/30. Data processing and analysis was done using SPSS version 16.The study reveals that 92% of women were involved in agriculture and 80% of them were illiterate. Ninety five percent of the women got marriage before the age of 20, 92.5% women became pregnant more than 3 times, 70% of babies were born at. Ninety two percent of the women gave birth to first child before the age of 20 and 90% respondents reported that they were involved in heavy work during pregnancy and postnatal period. Contributing factors depicted by our study were heavy work, illiteracy, early marriage/child birth, inadequate food during pregnancy and postpartum period, multi parity, home delivery and less rest period during post partum.